Inter-Religious Paradigm for Prevent Church Exclusivity in Disruptive Era - Silvia Daido (Conference Series, 2020)
Nowadays the public sphere has no boundaries and causes two branch dialogue of exclusiveness. Meanwhile, public spaces in the disruption era forced countries in the world in educational institutions and the socio-cultural values of social life. The Church's problem nowadays is stagnation and strength in maintaining tradition because the church is an organization that is over 75 to 100 years old. The church becomes exclusive by considering its religion as the only true religion and other religions as a way of heresy. Whereas in understanding nationalism in a pluralistic country such as Indonesia, this exclusiveness actually ends in fanaticism that is closed with tolerance. Church exclusivism in the understanding of Christian theology in the midst of religious pluralism often becomes an obstacle to the relationship of civilization in interpreting the pluralism of religions. The model of exclusivism-inclusivism-pluralism or universalism category in ‘acceptance model’ is necessary in teaching education. In higher education, the most effective model is interreligious. If the multireligious model emphasizes the teaching of religions that are descriptive, informative and objective about the doctrines, rituals and history of a particular religion, the inter-religious model goes further by emphasizing aspects of dialogue.